Tumor neuroendocrino con metástasis hepáticas revisión clínica y diagnostico con propuesta de aplicación de plan de cuidados de enfermería - Montaño Ordoñez, Ginger Mishel (2018)
Cancer is one of the diseases with the highest rate of morbidity and mortality in the world and with higher death rates in Third World countries. The present case analysis aims to analyze the evolution in a patient with neuroendocrine tumor and metastatic liver lesions, admitted to the Teófilo Dávila Hospital in the city of Machala and later referred to the Solca Machala Hospital; by reviewing your medical history including a proposal for an individualized nursing care plan. Worldwide statistics report an incidence ranging from 2 to 5 cases per 100,000 inhabitants, estimating that neuroendocrine tumors make up less than 1% of all types of cancer, becoming interesting and challenging for clinical practice, generally occurring in the third and fourth decade of life as it happened in this case. In Ecuador, there is no research that helps this type of work that allows the knowledge and application of nursing care in a timely manner. Neuroendocrine tumors occur by neuroendocrine cells that cause a hormonal hypersecretion mainly of serotonin forming clinical symptoms such as diarrhea, redness, stomach pain that present as a carcinoid syndrome due to portal metastasis product of this tumor, these are daily symptoms that can give differential diagnoses and that without adequate studies can hinder the timely diagnosis of the neoplasm. They can originate in endocrine glands, gastrointestinal tract, biliary tract, lung and bronchi, thymus, urogenital tract, the hereditary factor is the main risk factor while the treatment in these cases consists of chemoembolization, radioembolization, and surgery. The methodology used for the case analysis was the qualitative descriptive study due to the characterization of the disease. The case we present is of a young adult woman with a 1 month evolution characterized by clinical symptoms of carcinoid syndrome, which are treated symptomatically in a particular way until a clinical diagnosis supported by imaging and histology studies that helped a diagnosis definitive neuroendocrine tumor and metastasis. For the study was based on the before, during and after the disease based on the theory of the natural history of the disease with a focus on nursing care, an analysis of the importance of the role of the nurse was made in this type of pathology difficult to diagnose slow course and poor prognosis, applying the principle of assessment of the needs of Virginia Henderson. The activities carried out for this type of patients must be handled by specialized professionals in oncology nursing, since the management of this type of pathology makes the difference in the care to be carried out within the hospital and palliative care areas among them; emotional support, administration of medications such as oncology and pain therapy, fluid management, psychological support to the patient and family with coping and preparation for grief. In nursing care, the most compromised domains are visualized in the patient, describing it through the process of tumor evolution as well as the domain of elimination, rest and sleep, activity - exercise, role - relationships, adaptation - tolerance, comfort.